2010
DOI: 10.1002/chem.200903502
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine‐Containing Polyisocyanides as Versatile Nanoplatforms for Chromophoric and Bioscaffolding

Abstract: The straightforward syntheses of polyisocyanides containing the alanine-cysteine motif in their side chains have been achieved. Detailed characterization of the polymers revealed a well-defined and highly stable helical conformation of the polyimine backbone responsible for the formation of rodlike structures of over one hundred nanometers. The 4(1) helix is further stabilized by beta-sheet-like interactions between the peptide arms. As a result, the cysteine sulfur atoms are regularly aligned along the polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Circular dichroism (CD) is sensitive to the helical backbone conformation, and the CD spectra on the polymers deny a 1 : 1 distribution of two different helices, while on the other, the doubled resonances are close to a 1 : 1 ratio. Literature data also report on a preferred type of PICs' helix depending on the pendant groups …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Circular dichroism (CD) is sensitive to the helical backbone conformation, and the CD spectra on the polymers deny a 1 : 1 distribution of two different helices, while on the other, the doubled resonances are close to a 1 : 1 ratio. Literature data also report on a preferred type of PICs' helix depending on the pendant groups …”
Section: Resultsmentioning
confidence: 99%
“…Since then, a great variety of helical macromolecules was published . A well‐known class of synthetic helical polymers is based on polyisocyanides (PICs) . Upon the polymerization of the isocyanide monomers, a twisted structure is formed as a result of the merry‐go‐round mechanism at the nickel catalyst center .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of up to seven discrete protein bands indicates as well the assembly of multiple discotics into longer stacks, which enable the binding of at least seven monovalent streptavidins. The formation of discrete protein bands is in contrast to biotinylated polymers [40], which when bound to labeled streptavidin result in a smear on the gel. This indicated that the formed supramolecular polymers are much smaller than the size of streptavidin, which through their larger size are the main size determining factor.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, dipeptide isocyanide bearing cysteine derivatives with an S -ethyl carbamate protecting group have been recently described for the synthesis of polyisocyanides. 19 In another report, ( R )-methyl 3-(benzythio)-2-isocyanopropanoate was described for the synthesis of corresponding isoselenocyanate. 20 However, benzyl protection for thiol is not promising for many postmodifications on sulfur.…”
Section: Introductionmentioning
confidence: 99%